PERANCANGAN PUSAT INDUSTRI KREATIF DI KABUPATEN SAMOSIR: PERANCANGAN PUSAT INDUSTRI KREATIF DI KABUPATEN SAMOSIR - Rusdanisari, Anna; Ambarita, Desna; Hamidah, Noor; Harysakti, Ave (JURNAL PERSPEKTIF ARSITEKTUR, 2023)
The people in Parapat Village do not yet have a place to accommodate Batak art and culture. The design of the Cultural Museum was designed as a place to accommodate curiosity about Batak culture, and to find out about the richness of Batak culture. The interest from the public and tourists to the cultural heritage in North Sumatra is an effort to maintain and preserve the culture of the Batak tribe. The Batak Culture Museum in Parapat, Simalungun Regency, is a facility used for the preservation of Batak culture, and a means of educating Batak culture as well as a means of developing arts and culture. The Batak Culture Museum provides facilities for the public in the form of an entertainment room design that provides information on various kinds of culture of the Batak people, educational space for the public/tourists to study Batak culture. The method used is a qualitative method based on literature studies, comparative studies and precedent studies to explore the design approach and architectural design of the Batak culture museum. The output is the design of the Batak Culture Museum in Parapat, Simalungun Regency with a Neo-Vernacular Architectural Approach.